The Role of Interpersonal Communication in Improving Work Effectiveness in an Organizational Environment - Hayu Lusianawati (Journal of Dialogos, 2025)
Interpersonal communication is a crucial factor influencing work effectiveness in an organizational setting. This study uses a literature review method to analyze the contribution of interpersonal communication to coordination, employee psychological dynamics, and the achievement of organizational goals. The literature sources used include scientific journals, academic books, proceedings, and relevant publications from the past ten years. The analysis results show that effective interpersonal communication facilitates work coordination, improves task clarity, and minimizes misinterpretation of instructions. Harmonious interpersonal relationships increase motivation, trust, and job satisfaction, thus motivating employees to contribute optimally. In addition, interpersonal communication supports cross-divisional collaboration, accelerates decision-making, and strengthens the implementation of organizational strategies. Literature findings confirm that good interpersonal communication management plays a strategic role in improving individual and team performance, reducing internal conflict, and facilitating adaptation to changes in the work environment. This study concludes that interpersonal communication is not only a technical aspect, but also psychological and strategic factors that contribute significantly to the achievement of organizational goals. The implications of this research emphasize the need to improve interpersonal communication competencies for employees and management as part of an organizational development strategy